Employing ChatGPT In Developing Critical Thinking Skills Among International Students At King Saud University/ توظيف تطبيقات تشات جي بي تي في تنمية مهارات التفكير الناقد لدى الطلبة الدوليين بجامعة الملك سعود - Al-Shamrani, Saleh Abdullah (Ijaz Arabi Journal of Arabic Learning, 2025)
This study aimed to explore the possibility of using artificial intelligence applications, especially the ChatGPT model, to develop critical thinking skills among international students at King Saud University. Students’ interactions with ChatGPT were analyzed and their ability to enhance critical thinking and its development was evaluated, as the ChatGPT model works to generate linguistic responses. Natural and logical based on the inputs provided to discuss different topics and analyze problems related to different fields of study. The study was implemented on a diverse sample of (45) international students studying at King Saud University in the Kingdom of Saudi Arabia. The results of the study showed that applications of artificial intelligence (ChatGPT) had a positive impact on the development of critical thinking skills among international students, with an increase in agreement with statements regarding its benefits and its integration into their daily lives.